2019
DOI: 10.2147/cmar.s208677
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sorcin: a novel potential target in therapies of cancers</p>

Abstract: Soluble resistance-related calcium-binding protein (sorcin) is a member of the penta-EF-hand protein family. Sorcin is widely distributed in normal human tissues, such as the brain, heart, lymphocytes, kidneys, breast and skin. Findings suggest that sorcin is associated with the regulation of calcium homeostasis, cell cycle and vesicle trafficking. It has been reported that many types of non-neoplastic diseases such as diabetes, viral infection, infertility, and nervous system diseases were affected by the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…As mentioned above, sorcin is widely distributed in human tissues. Several studies propose its involvement in Ca 2+ homeostasis, cell cycle regulation and vesicle trafficking, diabetes, infertility and nervous system pathologies (reviewed in [ 40 ]), although most studies on sorcin are related to its overexpression in tumor cells [ 2 , 40 , 41 ] and to its regulatory role in excitation–contraction coupling in the heart through its interaction with several proteins, such as the SERCA pump [ 16 ], the ryanodine receptor intracellular Ca 2+ channel [ 15 , 42 ], the Na + -Ca 2+ exchanger [ 18 ] and L-type Ca 2+ channels [ 43 ]. Mass spectrometric and database analyses have shown that sorcin is highly expressed in the brain [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, sorcin is widely distributed in human tissues. Several studies propose its involvement in Ca 2+ homeostasis, cell cycle regulation and vesicle trafficking, diabetes, infertility and nervous system pathologies (reviewed in [ 40 ]), although most studies on sorcin are related to its overexpression in tumor cells [ 2 , 40 , 41 ] and to its regulatory role in excitation–contraction coupling in the heart through its interaction with several proteins, such as the SERCA pump [ 16 ], the ryanodine receptor intracellular Ca 2+ channel [ 15 , 42 ], the Na + -Ca 2+ exchanger [ 18 ] and L-type Ca 2+ channels [ 43 ]. Mass spectrometric and database analyses have shown that sorcin is highly expressed in the brain [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review describes how these reporters could be used to pinpoint Ca 2+ sensitive processes in mitosis, such as when GCaMP6 tethered to actin, nucleated at centrosomes and detected Ca 2+ signals thought to play a role in orienting the mitotic spindle (Farina et al, 2016;Helassa et al, 2019;Lagos-Cabre et al, 2020). The authors also emphasise the importance of Ca 2+ binding proteins in mitosis, dysregulation of which may affect protein kinase activation (Lee et al, 2014;Zhou et al, 2019), altered gene expression and ultimately oncogenesis and the development of anti-cancer drugs which target Ca 2+ signalling components is a burgeoning field of therapeutics (Roderick and Cook, 2008;Monteith et al, 2017).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…In addition to calmodulin and CaBP7, a variety of other small calcium sensing proteins have been linked to mitosis progression. Sorcin, a small penta-EF hand calcium sensor, exhibits mitosis specific changes in cellular localisation (Lalioti et al, 2014) and is over-expressed in multiple human cancers (Zhou et al, 2019). It has been linked to the multidrug resistant phenotype of certain cancers and is therefore of significant interest as a clinically relevant target (Pomeroy et al, 2002;Tan et al, 2003;Yokota et al, 2006;Nagpal and Das, 2007;Zhou et al, 2019).…”
Section: Calcium Signals Exist During Mitosis Whatmentioning
confidence: 99%
“…Sorcin, a small penta-EF hand calcium sensor, exhibits mitosis specific changes in cellular localisation (Lalioti et al, 2014) and is over-expressed in multiple human cancers (Zhou et al, 2019). It has been linked to the multidrug resistant phenotype of certain cancers and is therefore of significant interest as a clinically relevant target (Pomeroy et al, 2002;Tan et al, 2003;Yokota et al, 2006;Nagpal and Das, 2007;Zhou et al, 2019). Early in mitosis, sorcin-positive vesicles associate with the spindle and later, at cytokinesis, they are found in the cleavage furrow and at the midbody (Lalioti et al, 2014).…”
Section: Calcium Signals Exist During Mitosis Whatmentioning
confidence: 99%